Phylogenomic analysis of phenylalanine ammonia-lyase (PAL) multigene family and their differential expression analysis in wheat (Triticum aestivum L.) suggested their roles during different stress responses - Zhan, Chuang; Li, Yiting; Li, Han; Wang, Mengru; Gong, Shuangjun; Ma, Dongfang; Li, Yan (Frontiers in Plant Science, 2022)
Phenylalanine ammonia-lyase (PAL) is a key enzyme in the phenylalanine metabolism pathway and plays an important role in plant growth and stress response. It has been widely reported in plants, but less studied in wheat. In this study, 54 PAL genes were identified in the wheat genome. Based on phylogenetic analysis, the 54 TaPAL genes were divided into four groups (Ⅰ, Ⅱ, Ⅲ, and Ⅳ). Then, the expression levels of TaPALs under biotic stresses were analyzed by transcriptome data analysis. The results showed that 31 genes were up-regulated and one gene was down-regulated after inoculation with Fusarium graminearum, 11 genes were up-regulated and 14 genes were down-regulated after inoculation with Puccinia striiformis, and 32 up-regulated and three down-regulated genes after inoculation with powdery mildew. The expression patterns of the five TaPALs were further analyzed by qRT-PCR. After inoculation with F. graminearum, the expression levels of five TaPALs were up-regulated. However, the TaPALs (expect TaPAL49) were down-regulated when inoculated with P. striiformis. Finally, the functions of TaPAL32 and TaPAL42 in resistance of wheat to the stripe rust were further analyzed by virus induced gene silencing (VIGS) assays. The results showed that the disease severity of TaPAL32 and TaPAL42 silenced plants was higher than that of control plants at 14 days after inoculation. It indicated that these two genes played a positive role in wheat stripe rust resistance. This study provided new evidence support for the functional study of PAL genes in wheat, and provided potential application value for the breeding of wheat resistant varieties.